Numerical Evaluation of R152a-Al2O3 Nanorefrigerant for Energy Efficiency Enhancement in Vapour Compression Refrigeration Systems - Redjeb, Youcef; Khaled, Aymen; Khaled, Bilal; Serouti, Abdelghani; Ferhat, Mohammd Fouad (University of Boumerdes, 2025)
This work conducts an investigation into the thermodynamic performance of a vapour compression refrigeration system (VCRS) using R152a enhanced with Al2O3 nanoparticles as a possible replacement for conventional fluids due to its low GWP fluids besides the benefits of incorporating nanoparticles in terms of thermal conductivity, heat transfer, and improved system efficiency. In this work, a comprehensive MATLAB code linked with the REFPROP database has been developed as a means to simulate the effects of incorporating nanoparticle within the selected refrigerants on key performance parameters of the VCRS. The analysis was performed taking into consideration standard operating conditions, and a mass fraction of Al2O3 nanoparticles ranging between 0.1wt% and 0.5wt%. The primary performance indicators considered in this study were the coefficient of performance (COP), compressor power consumption, and heat absorbed at the evaporator. The results revealed a remarkable enhancement in system behaviour with the incorporation of nanoparticles. At a mass fraction of 0.5 wt%, the COP increased by approximately 6.9% compared to the 0.1 wt% case. This improvement was associated by a significant reduction in compressor power consumption of about 7.5%, indicating an efficiency gain in energy use. Interestingly, the heat absorbed at the evaporator remained practically constant across the investigated range. These outcomes revealed that R152a–Al2O3 nanorefrigerants provide a promising pathway to improve energy efficiency of VCRS without compromising its thermal performance. The reduction in compressor power shows potential operational benefits, including lower electricity costs and reduced mechanical stress on components, which may extend system lifetime. In conclusion, the present work demonstrates the potential of nanorefrigerants as possible alternatives to conventional refrigerants for sustainable refrigeration systems. The results provide meaningful theoretical insights that bridge the gap between simulation and application, supporting further research toward environmentally friendly and energy-efficient cooling technologies. الملخص: يتناول هذا العمل دراسة الأداء الثرموديناميكي لنظام التبريد بالانضغاط البخاري (VCRS) باستخدام سائل التبريد R152a المعزز بجزيئات Al₂O₃ النانوية كبديل محتمل للسوائل التقليدية، نظرًا لانخفاض إمكانية احترارها العالمي (GWP)، إلى جانب الفوائد التي توفرها الجسيمات النانوية من حيث زيادة الموصلية الحرارية وتحسين انتقال الحرارة وكفاءة النظام. في هذا البحث، تم تطوير كود شامل باستخدام MATLAB مرتبط بقاعدة بيانات REFPROP بهدف محاكاة تأثير دمج الجسيمات النانوية داخل سوائل التبريد المختارة على المتغيرات الأساسية لأداء النظام. أُجري التحليل مع مراعاة ظروف التشغيل القياسية، وباستخدام كسور كتلية من جسيمات Al₂O₃ تتراوح بين 0.1% و0.5%. وقد تم التركيز على ثلاثة مؤشرات أداء رئيسية: معامل الأداء (COP)، استهلاك طاقة الضاغط، والحرارة الممتصة في المبخر. أظهرت النتائج تحسنًا ملحوظًا في سلوك النظام مع إضافة الجسيمات النانوية. فعند كسر كتلي قدره 0.5%، ازداد معامل الأداء بنسبة تقارب 6.9% مقارنة بحالة 0.1%. وارتبط هذا التحسن بانخفاض كبير في استهلاك طاقة الضاغط بنسبة حوالي 7.5%، مما يدل على تحسن في كفاءة استخدام الطاقة. ومن المثير للاهتمام أن الحرارة الممتصة في المبخر بقيت شبه ثابتة ضمن نطاق الدراسة. تُظهر هذه النتائج أن مزيج R152a–Al₂O₃ يمثل مسارًا واعدًا لتحسين كفاءة الطاقة في أنظمة التبريد بالانضغاط البخاري دون التأثير سلبًا على الأداء الحراري. كما أن انخفاض استهلاك طاقة الضاغط يشير إلى فوائد تشغيلية مهمة، مثل تقليل تكاليف الكهرباء وخفض الإجهاد الميكانيكي على المكونات، مما قد يطيل عمر النظام التشغيلي. في الختام، يبرهن هذا العمل على إمكانات المبردات النانوية كبدائل مستقبلية للمبردات التقليدية في أنظمة تبريد مستدامة. وتوفر النتائج رؤى نظرية ذات قيمة تُسهم في ردم الفجوة بين المحاكاة والتطبيق العملي، وتدعم الأبحاث المستقبلية نحو تطوير تقنيات تبريد صديقة للبيئة وأكثر كفاءة في استهلاك الطاقة.
Intervention
Keywords: R152a; Al2O3 nanoparticles; nanorefrigerants; VCRS; COP.; جسيمات Al₂O₃ النانوية; المبردات النانوية; نظام التبريد بالانضغاط البخاري VCRS; معامل الأداء COP